Theory of circuit block switch-off - S. Henzler; J. Berthold; G. Georgakos; D. Schmitt-Landsiedel (Advances in Radio Science, 2004)
Switching-off unused circuit blocks is a promising approach to supress static leakage currents in ultra deep sub-micron CMOS digital systems. Basic performance parameters of Circuit Block Switch-Off (CBSO) schemes are defined and their dependence on basic circuit parameters is estimated. Therefore the design trade-off between strong leakage suppression in idle mode and adequate dynamic performance in active mode can be supported by simple analytic investigations. Additionally, a guideline for the estimation of the minimum time for which a block deactivation is useful is derived.